على الغدد اللبنية لعذارى الجرذان Calendula officinalis تأثير الخلاصة المائية لنبات الأقحوان - الحبوبي بان طالب (Al-Nahrain Journal of Science, 2018)
The effect of aqueous extract of Calendulaofficinalis on the growth and development ofmammary glands was studied. 12 albino ratswere used in this study, divided into twogroups, the control group was given tap waterand the other group received the extract orallyfor 14 days. The result revealed that theaqueous extract affect the number and size ofthe alveoli of the mammary glands comparedto control. The mean alveoli diameter oftreated animal was significant 36.22 mcompared to 20.11 m of control p<0.05. Inaddition the mean of nuclei was 17.1 in treatedanimals compared to 10.1 in the control,significant increase p<0.05 in levels ofestradiol, progesterone and prolactin hormonesin treated animals compared to control.Estrogen and progesterone receptorsexpression revealed equalitive decrease intreated animals compared to control, when theestrogen and progesterone receptor expressionamong the control virgin rats were highlyexpression (+++), it decreased in expression(+) in treated animals.